The Effect Of Investment Motivation, Financial Literacy, And Understanding Of Sharia Investment On Investment Interest With Self-Efficacy As A Moderating Variable - Afriyani, Iin; Sofyan, Syaakir; Hidayah, Noor Riefma (Journal of Contemporary Economics and Business Management, 2026)
Study This aim for analyze influence motivation investment, literacy finance, and understanding sharia investment towards interest invest through digital applications for students Faculty of Islamic Economics and Business (FEBI) Datokarama State Islamic University (UIN) Palu, with self-efficacy as variables moderation. Research This use approach quantitative with method survey. Population is all over FEBI UIN Datokarama Palu students who have not yet Once invest in a way active. Sample selected use technique purposive sampling and data collected through questionnaire likert scale. Data analysis using Multiple Linear Regression and Moderated Regression Analysis (MRA) with SPSS 26 assistance. Research results show that motivation investment and literacy finance influential positive and significant to interest invest, while understanding sharia investment does not influential significant in a way partial. In simultaneously, all variables independent together self-efficacy as moderation influential significant to interest invest with contribution by 89.7%. Self-efficacy is proven moderate and strengthen influence motivation investment, but weaken influence literacy finance, as well as no capable moderate influence understanding sharia investment towards interest invest through digital applications.